Use of epidemiological data as the basis for developing a medical curriculum - Machado, José Lúcio Martins; Souza, Sonia Regina Pereira de; Brenna, Sylvia Michelina Fernandes; Pose, Regina Albanese; Bollela, Valdes Roberto; Vieira, Joaquim Edson (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Epidemiology may help educators to face the challenge of establishing content guidelines for the curricula in medical schools. The aim was to develop learning objectives for a medical curriculum from an epidemiology database. DESIGN AND SETTING: Descriptive study assessing morbidity and mortality data, conducted in a private university in São Paulo. METHODS: An epidemiology database was used, with mortality and morbidity recorded as summaries of deaths and the World Health Organization’s Disability-Adjusted Life Year (DALY). The scoring took into consideration probabilities for mortality and morbidity. RESULTS: The scoring presented a classification of health conditions to be used by a curriculum design committee, taking into consideration its highest and lowest quartiles, which corresponded respectively to the highest and lowest impact on morbidity and mortality. Data from three countries were used for international comparison and showed distinct results. The resulting scores indicated topics to be developed through educational taxonomy. CONCLUSION: The frequencies of the health conditions and their statistical treatment made it possible to identify topics that should be fully developed within medical education. The classification also suggested limits between topics that should be developed in depth, including knowledge and development of skills and attitudes, regarding topics that can be concisely presented at the level of knowledge.